Feeding ecology of the freshwater crab Trichodactylus borellianus (Decapoda: Trichodactylidae) in the floodplain of the Paraná River, southern South America. - Williner, Verónic (2013)
Freshwater crabs are not commonly considered to be an important group in trophic webs,where this might be due to a lack of knowledge about their trophic roles in aquatic ecosystems. Trichodactylus borellianus is one of the most common and widely distributed freshwater crabs in the floodplains of the southern South American rivers. The main objective of the present study was to examine the trophic role of T. borellianus in the floodplain of the Paraná River and its relationships with the freshwater littoral community. The trophic spectrum of this species was characterised for both sexes and individuals of different sizes (adults and juveniles) throughout the daily and seasonal cycles. Samples were collected from the aquatic vegetation of three shallow lakes. Using a stereomicroscope, the diet composition and the feeding activity of T. borellianus were evaluated through the examination of the stomach contents and their degree of emptiness. This crab consumes several plant and animal items, including amoebas, rotifers, oligochaetes, copepods, cladocerans, and insect larvae.Moreover, this species consumes filamentous and unicellular algae, diatoms, fungi, and macrophytic remains. The predatory habits varied with the season and time of day, and variations in the feeding activity of the juveniles and adults were detected and documented. The diversity of food items eaten by this crab suggests that its trophic role in the community as an omnivore and opportunistic predator provides a connection among several trophic levels from both aquatic and terrestrial communities.